Needs Analysis of the Bengkulu Community Through the Lens of Local Culture - Saepudin Sae; M. Azizzullah Ilyas; Edi Sumanto; Meri Lestari (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: Graduate profiles that do not match the needs of the world of work in a community environment based on local culture are one of the problems for prospective teachers. This research aims to analyze local culture-based community responses regarding the development of prospective teachers' skills. Methodology: This research used a mixed-method approach with primary data from questionnaires and secondary data from observations, interviews, and documentation. Main Findings: This study revealed that out of a sample of 100 students, 83.33% responded positively to the implementation of status changes. Additionally, 65% of the community acknowledged that the status change would lead to a greater variety of academic programs. Meanwhile, 9% of the community believed that this change would contribute to improved welfare, and 75.5% recognized its overall benefits. Insights from stakeholder interviews led to the recommendation of five study programs, while surveys of 11th and 12th-grade prospective students identified ten preferred study programs. Novelty/Originality of this study: The novelty of this research lies in its integration of local cultural perspectives into the needs analysis for developing study programs in Islamic universities. Unlike conventional needs assessments that focus solely on market demands, this study uniquely examines how cultural values and community expectations shape the required competencies of prospective teachers.